Penerapan Metode OCRA untuk Rekomendasi Café & Coffee Shop Terbaik di Kota Metro - Yaritsha Zahra, Nazwa; Muharni, Sita (Jurnal Informatika, 2026)
Abstract —  The café and coffee shop industry in Metro City has experienced rapid growth in recent years, in line with changing habits among students and workers, who increasingly use cafés as places to study, work, discuss, and socialize. This trend offers consumers a wide range of choices but also makes the process of selecting the best café more complex, as evaluations are often influenced by personal preferences and reviews that may not be entirely objective. Based on these conditions, this study aims to identify relevant evaluation criteria and apply the Operational Competitiveness Rating Analysis (OCRA) method to generate recommendations for the best cafes in Metro City. This study employs a quantitative approach with a descriptive-comparative design. Data were collected via a closed-ended Likert-scale questionnaire administered to 50 respondents—comprising students and workers—and supplemented with secondary data from digital platforms. Six criteria were used in the analysis: price as a cost attribute, and taste quality, service, facilities, location, and customer ratings as benefit attributes.The results of the study show that, out of the 15 initial alternatives, 9 cafés met the data eligibility criteria for further analysis. Based on OCRA calculations, Bongsu Signature received the highest preference score of 0.9353, followed by Ffaux Society at 0.9334 and Timeless Coffee Bar at 0.8878. These findings indicate that the OCRA method is capable of generating systematic, measurable, and relatively objective recommendations, thereby reinforcing the role of MCDM-based decision support systems for both consumers and local café operators in Metro City. Managerially, the findings can serve as an evaluation reference for local café operators to improve service quality, facilities, and product quality, which strongly influence consumer preferences.   Keywords — OCRA, decision support system, café, MCDM, decision making.